The significance of self-financing for the development of the University of Defense operating capacities - Neševski Aleksandar; Milenković Dragana; Knežević Milena (Ekonomija: teorija i praksa, 2023)
The operation of the University of Defense largely depends on the funds determined by the budget of the Republic of Serbia. For its successful functioning, it is necessary to provide regularity and timeliness of its financing as a budget user. Besides the budget, as its basic source of financing, the University of Defense has to rely on different funds and other sources of financing. Funds from other sources, although much lower compared to the state budget funds, are extremely important for certain expenses. The subject of this paper is to analyze the possibility of financing the University of Defense with its own incomes, as an additional source of funding. The limiting factor is the fact that all realized incomes of the University cannot be used to finance its operations, but only part of income incurred from education and scientific research. The normative regulation of this field in the defense system is not favorable for the University of Defense. Compared to other universities in the Republic of Serbia and the region, the University of Defense does not have a sufficient level of autonomy in bringing decisions related to the allocation of its own financial resources. In the following period, the University of Defense needs to take appropriate steps to increase its own revenues and thereby partially overcome the problem of insufficient budget funds. Another important task for the University of Defense is to initiate a procedure for additional normative regulations aimed at using its own revenues.